ANALISIS KESULITAN SISWA DALAM MENGIDENTIFIKASI IDE POKOK PARAGRAF PADA TEKS EKSPOSISI DI KELAS V SD NEGERI NEUSOK TEUBALUI KABUPATEN ACEH BESAR - Riama Sinta Saragih; Mislinawati; Hasniyati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze students’ difficulties in identifying the main idea of paragraphs in expository texts in grade V of SD Negeri Neusok Teubalui, Aceh Besar, and to determine the factors causing these difficulties. This research employed a qualitative approach with a descriptive design. The subjects of this study were 23 fifth-grade students. Data were collected through observation, interviews, and tests, while data analysis used the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The results showed that students’ ability to identify the main idea of paragraphs was still at a moderate level, with an average score of 63. The highest level of difficulty was found in identifying the main idea in deductive paragraphs (95.65%) and inductive paragraphs (91.30%). In addition, students also experienced difficulties in mixed paragraphs (65.21%) and in distinguishing between main sentences and supporting sentences (43.50%). These findings indicate that most students have not yet been able to fully understand the content of the text. The factors causing these difficulties include linguistic factors such as limited vocabulary and the influence of local language, cognitive factors related to low ability in understanding relationships between sentences, metacognitive factors such as lack of effective reading strategies, and affective factors such as low reading interest. Therefore, improvements in reading comprehension instruction with more effective and varied strategies are needed to enhance students’ ability in identifying main ideas